On the effect of N-GaN/P-GaN/N-GaN/P-GaN/N-GaN built-in junctions in the n-GaN layer for InGaN/GaN light-emitting diodes - Kyaw, Zabu (2014)
N-GaN/P-GaN/N-GaN/P-GaN/N-GaN (NPNPN-GaN) junctions embedded between the n-GaN region and multiple quantum wells (MQWs) are systematically studied both experimentally and theoretically to increase the performance of InGaN/GaN light emitting diodes (LEDs) in this work. In the proposed architecture, each thin P-GaN layer sandwiched in the NPNPN-GaN structure is completely depleted due to the built-in electric field in the NPNPN-GaN junctions, and the ionized acceptors in these P-GaN layers serve as the energy barriers for electrons from the n-GaN region, resulting in a reduced electron over flow and enhanced the current spreading horizontally in the n- GaN region. These lead to increased optical output power and external quantum efficiency (EQE) from the proposed device.